Synthesis, characterization and thermal behaviour on solid tartrates of some bivalent metal ions - Rodrigues, Emanuel C.; Carvalho, Claudio T. [UNESP]; de Siqueira, Adriano B.; Bannach, Gilbert [UNESP]; Ionashiro, Massao [UNESP] (Elsevier B.V., 2009)
Solid-state M-L compounds, where M stands for bivalent Mn, Fe, Co, Ni, Cu, Zn and L is tartrate, have been synthesized. Thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy, elemental analysis and complexometry were used to characterize and to study the thermal behaviour of these compounds. The TG-DTA and DSC curves show that the manganese, cobalt and nickel compounds are hydrated while iron, copper and zinc ones are anhydrous. The thermal stability of the anhydrous compounds depends on the nature of the metal ion, and it follows the order: Zn > Cu > Mn = Co > Ni > Fe. These Curves also show that the thermal decomposition Occurs in a single step to the respective metal oxides. The results led to information about the composition, dehydration, ligand denticity and thermal decomposition of the isolated compounds. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bivalent metals; Tartrate; Characterization; Thermal behaviour